A microbial gene catalog of anaerobic digestion from full-scale biogas plants. Issue 1 (27th January 2021) - Ma, Shichun; Jiang, Fan; Huang, Yan; Zhang, Yan; Wang, Sen; Fan, Hui; Liu, Bo; Li, Qiang; Yin, Lijuan; Wang, Hengchao; Liu, Hangwei; Ren, Yuwei; et al.
Abstract: Background: Biogas production with anaerobic digestion (AD) is one of the most promising solutions for both renewable energy production and resolving the environmental problem caused by the worldwide increase in organic waste. However, the complex structure of the microbiome in AD is poorly understood. Findings: In this study, we constructed a microbial gene catalog of AD (22, 840, 185 genes) based on 1, 817 Gb metagenomic data derived from digestate samples of 56 full-scale biogas plants fed with diverse feedstocks. Among the gene catalog, 73.63% and 2.32% of genes were taxonomically annotated to Bacteria and Archaea, respectively, and 57.07% of genes were functionally annotated with KEGG orthologous groups. Our results confirmed the existence of core microbiome in AD and showed that the type of feedstock (cattle, chicken, and pig manure) has a great influence on carbohydrate hydrolysis and methanogenesis. In addition, 2, 426 metagenome-assembled genomes were recovered from all digestate samples, and all genomes were estimated to be ≥80% complete with ≤10% contamination. Conclusions: This study deepens our understanding of the microbial composition and function in the AD process and also provides a huge number of reference genome and gene resources for analysis of anaerobic microbiota.